THE DIFFERENCE IN CONSUMER RISK PERCEPTION BETWEEN CELEBRITY ENDORSER AND EXPERT ENDORSER IN COLLEGE ADVERTISEMENTS - Euis Soliha; Naila Zulfa (Journal of Indonesian Economy and Business (JIEB), 2009)
This research aims to examine the difference in consumer risk perception between celebrity and expert endorser in advertisement. We proposed two hypothesis, H1: There is a difference in consumer risk perception between an expert endorser and celebrityendorser in college advertisement. H2: There is a difference in consumer risk perception between an expert endorser and a celebrity endorser in college advertisement, which is moderated by the consumer product knowledge.Experimental design was employed in this study with Statistical Experimental-Completely Randomized Design. This was conducted on three groups to test H1 and six groups to test H2. To test H1, the participant of each group was given full color print ads using celebrity endorser, expert endorser and nonendorser in advertisement. We gofurther splitting each group with high and low consumer product knowledge to test H2.The participants of this research are 200 students of SMA 7 Semarang. We use One Way Anova to test H1 and two ways Anova to test H2. Our findings showed that there is a difference in consumer risk perception between an expert endorser and celebrity endorser in college advertisement. We also found that there is no differencein consumer risk perception between an expert endorser and a celebrity endorser in college’s advertisement, which is moderated by the consumer product knowledge. We also found that there is difference in consumer’s perceived performance risk, consumer’sperceived financial risk and consumer’s social risk between an expert and celebrity endorser in College advertisement. On the other hand, we found there is no difference in consumer perceived psychological risk between an expert and celebrity endorser in College advertisement.Keywords: celebrity endorser, expert endorser, consumer risk perception, consumer product knowledge.